Photocaged Hoechst Enables Subnuclear Visualization and Cell Selective Staining of DNA in vivo. (2nd November 2020) - Lämmle, Carina A.; Varady, Adam; Müller, Thorsten G.; Sturtzel, Caterina; Riepl, Michael; Mathes, Bettina; Eichhorst, Jenny; Sporbert, Anje; Lehmann, Martin; Kräusslich, Hans‐Georg; Distel, Martin; Broichhagen, Johannes
Abstract: Selective targeting of DNA by means of fluorescent labeling has become a mainstay in the life sciences. While genetic engineering serves as a powerful technique and allows the visualization of nucleic acid by using DNA‐targeting fluorescent fusion proteins in a cell‐type‐ and subcellular‐specific manner, it relies on the introduction of foreign genes. On the other hand, DNA‐binding small fluorescent molecules can be used without genetic engineering, but they are not spatially restricted. Herein, we report a photocaged version of the DNA dye Hoechst33342 (pcHoechst), which can be uncaged by using UV to blue light for the selective staining of chromosomal DNA in subnuclear regions of live cells. Expanding its application to a vertebrate model organism, we demonstrate uncaging in epithelial cells and short‐term cell tracking in vivo in zebrafish. We envision pcHoechst as a valuable tool for targeting and interrogating DNA with precise spatiotemporal resolution in living cells and wild‐type organisms. Abstract : Precision without genetic engineering : pcHoechst allows light‐triggered DNA staining by photochemical uncaging. As such, it can be used to visualize and track nuclei with cellular resolution, which is demonstrated in live cells and in vivo . This chemical tool does not rely on genetic engineering and can ultimately be used to target and track DNA in subnuclear regions with high resolution.